COMMUNICATIVE LANGUAGE TEACHING AS CONCEPTUALIZED BY BHUTANESE ENGLISH AS SECOND LANGUAGE TEACHERS - Jigme Dorji (Indonesian EFL Journal, 2017)
The purpose of this qualitative study was to examine the conceptualization of communicative language teaching (CLT) by the English as Second Language (ESL) teachers in Chukha district in Bhutan. Four ESL teachers were selected as the participants for the semi-structured interview through purposive sampling technique. A set of 15 predetermined open-ended questions on CLT were framed and asked based on Savignon’s (1983) Foreign Language Attitude Survey Test (FLAST). The content validity of interview questions was ensured by consulting three experts and computing Item Object Congruence (IOC) in accordance with Lynn’s (1986) item acceptability criteria. The data were analyzed using content analysis technique. The results revealed teachers’ conceptualization under two categories; in compliance with and deviance from CLT principles. Under first category, the results showed that the participants believed CLT as a language teaching approach that focuses on developing communicative competence, teaching language for real life, child-centered teaching, and teaching culture in the second language classroom. Under the second category, the results indicated that the participants believed CLT as not using mother tongue in teaching English and only teaching listening and speaking skills. In addition, the study also uncovered the fact that ESL teachers are not aware of CLT approach. The article concludes with the discussion on the areas of training particularly relevant to this group of Bhutanese ESL teachers and recommendations for future studies.      Keywords: communicative competence, communicative language teaching, conceptualization